Inheritance and mapping of Mj-2, a new source of root-knot nematode (Meloidogyne javanica) resistance in carrot - Ali, Aamir (2013)
Root-knot nematodes limit carrot production around the world by inducing taproot forking and galling deformities that render carrots unmarketable. In warmer climates, Meloidogyne javanica and Meloidogyne incognita are most prevalent. In F2 and F3 progeny from the cross between an Asian carrot resistant to M. javanica, PI 652188, and a susceptible carrot, resistance response was incompletely dominant with a relatively high heritability (H2 = 0.78) and provided evidence for a single gene, designated Mj-2, contributing to resistance. Molecular markers linked to the previously described root-knot nematode resistance gene, Mj-1 on chromosome 8 derived from Brasilia, demonstrated that Mj-2 does not map to that same locus but is on the same chromosome.